1997
DOI: 10.1046/j.1365-294x.1997.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic characterization of ineffective Frankia in Alnus glutinosa (L.) Gaertn. nodules from wetland soil inoculants

Abstract: Ineffective Frankia endophytes were retrieved from various wet soils by using Alnus glutinosa clones as trapping plants. No pure cultures could be isolated from these ineffective nodules. Therefore, the phylogenetic position of these endophytes was determined by sequence analysis of cloned PCR products of bacterial 16S rDNA, derived from nodules. The results showed that all nodule endophytes belong to a hitherto undescribed cluster of the Frankia phylogenetic tree. The position of these uncultured ineffective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…If alder is able to select genotypes based on optimal physiological beneWt in a given environment, such host choice would be a strong contributing 'Wlter' on the genetic structure of the symbionts. Both positive and negative selection of symbionts have been observed in legume-rhizobia interactions (Simms et al 2006;Kiers et al 2003) and A. glutinosa appears to exert negative selection on ineVective (non-N-Wxing) Frankia genotypes (Wolters et al 1997;van Dijk and Sluimer 1994). Positive symbiont selection by Alnus does not appear to have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…If alder is able to select genotypes based on optimal physiological beneWt in a given environment, such host choice would be a strong contributing 'Wlter' on the genetic structure of the symbionts. Both positive and negative selection of symbionts have been observed in legume-rhizobia interactions (Simms et al 2006;Kiers et al 2003) and A. glutinosa appears to exert negative selection on ineVective (non-N-Wxing) Frankia genotypes (Wolters et al 1997;van Dijk and Sluimer 1994). Positive symbiont selection by Alnus does not appear to have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Actinorhizal plants are therefore found often on sandy and wet soils where low levels of available nitrogen may preclude the growth of other species, and thus usually occur as pioneer vegetation at early stages of plant succession [4]. The formation of root nodules is host plant-specific, with frankiae of clusters 1, 2, and 3 representing nitrogen-fixing frankiae of the Alnus, Dryas, and Elaeagnus host infection groups [5], and those of cluster 4 representing non-nitrogen-fixing strains [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cluster 4 frankiae are scarce, even though they have been reported to form an important fraction of all frankiae in wet soils under A. glutinosa (33,34), with natural resistance to infection exhibited by different progenies of A. glutinosa (12,35). While these results were based on bioassays, we now also have the instruments to assess the importance of cluster 4 frankiae in different environments or to use different strains of the non-nitrogen-fixing frankiae in controlled inoculation studies to retrieve information on their ecology in soils.…”
Section: Discussionmentioning
confidence: 99%